2011
DOI: 10.1111/j.1610-0387.2011.07585_suppl.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenese des Pruritus

Abstract: Keywords• itch • pruritus • pain • atopic dermatitis • sensory nerves • urticaria Zusammenfassung Die Pathogenese von akutem und chronischem Pruritus (über 6 Wochen Dauer) ist komplex und involviert in der Haut ein Netzwerk aus residenten (z. B. Mastzellen, Keratinozyten, sensorische Neurone) und transienten inflammatorischen (z. B. eosinophile Granulozyten) Zellen. Aktuelle Untersuchungen konnten zeigen, dass sich trotz überlappender Mechanismen die Pathogenese von Pruritus und Schmerz in wesentlichen Punkten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…It has been shown that the impact on quality of life due to chronic pruritus is comparable to the impact of the chronic pain syndrome [5]. Pruritus and pain are complex sensations with both common and differing signaling pathways and characteristics [6]. The well‐known observation that scratching‐induced pain improves or temporarily abolishes pruritus demonstrates this.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the impact on quality of life due to chronic pruritus is comparable to the impact of the chronic pain syndrome [5]. Pruritus and pain are complex sensations with both common and differing signaling pathways and characteristics [6]. The well‐known observation that scratching‐induced pain improves or temporarily abolishes pruritus demonstrates this.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, for example, demonstrate that mechanosensitive pain neurons can transmit pruritus. In central imaging corresponding brain regions can be activated by pain and pruritus, and pruritus‐specific brain regions do not appear to exist [6]. Possible differences exist with respect to the activation of central motor areas.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations